2020
DOI: 10.3390/ijerph17249296
|View full text |Cite
|
Sign up to set email alerts
|

Application of Geostatistical Analysis and Random Forest for Source Analysis and Human Health Risk Assessment of Potentially Toxic Elements (PTEs) in Arable Land Soil

Abstract: Arable land soil is one of the most precious natural resources of Earth, it provides the fundamental material and numerous resources essential for the development of human society. To determine the pollution of potential toxic factors in the surface soil of cultivated land and its risks to human health, concentrations of five different potentially toxic elements (PTEs) were detected in 1109 soil samples collected in Xiangzhou, China, in 2019. In this study, health risk assessment was used to judge the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In addition, there is no need to make variable selection. The algorithm represents a convenient method of calculating the nonlinear effects of variables and can evaluate the importance of independent variables [ 41 , 42 ]. Thus, this method has good applicability for regression analysis based on big data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is no need to make variable selection. The algorithm represents a convenient method of calculating the nonlinear effects of variables and can evaluate the importance of independent variables [ 41 , 42 ]. Thus, this method has good applicability for regression analysis based on big data.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 8a, it can be seen that first-grade farmland based on RF was mainly distributed in Zhangwan, Guyi, and Longwang, while that based on EW was mainly distributed in Shuanggou, Chenghe, Guyi, Longwang, and Shiqiao (Figure 8c). Shuanggou and Chenghe are industrial towns in Xiangzhou with high urbanization and high intensity of farmland use, and existing studies have shown that the heavy-metal element content of farmland soil around the towns is high overall, so it is unreasonable for the farmland to be identified as first-grade land [44,55]. The topography of Shiqiao is high and the soil water and fertilizer retention ability is poor, so theoretically, the quality grade of farmland should be lower, which is consistent with the existing research results [56].…”
Section: Comparison Of Assessment Resultsmentioning
confidence: 99%
“…Xiangzhou belongs to Hubei Province, China. The research region has a subtropical humid monsoon continental climate with an annual average temperature of 15.3-5.8 • C and annual average precipitation of 800-900 mm [12]. The agricultural land is 202,807.25 hectares, accounting for 82.22% of the total land area.…”
Section: Study Locationmentioning
confidence: 99%